Increased Understanding of Indonesian Culture through the International Cultural Festival in Kumamoto Japan - Arrazy, Syafran; Siregar, Putra Apriadi; Hidayah, Widyatul (Jurnal Abdi Mas Adzkia, 2025)
The International Cultural Festival - Indonesia Negeriku, held at the Prefectural University of Kumamoto, Japan, in July 2023, aimed to introduce Indonesia's rich culture to the Japanese community, particularly school students in Kumamoto. The event featured various aspects of Indonesian culture, including traditional dance, music, cuisine, and angklung and batik performances. The festival not only introduced Indonesian culture but also promoted cultural diplomacy in an engaging and interactive manner. Evaluation through observation and interviews with visitors revealed that the activity increased their understanding and appreciation of Indonesia's cultural diversity. The use of digital media to showcase Indonesian flora and fauna further enriched participants' experiences, reinforced Indonesia's positive image in the eyes of the Japanese public, and strengthened relations between nations. By involving active community participation and government support, the festival succeeded in creating a platform for cultural dialogue that enhanced global understanding of Indonesia.